TINDAK PIDANA PERJUDIAN ONLINE DI KOTA MANADO TANTANGAN DAN UPAYA PENEGAKAN HUKUM - Gubali, Agustina Waty U. (Program Studi Ilmu Hukum Universtitas Muhammadiyah Gorontalo, 2024)
Online gambling is one of the forms of digital crime that is increasingly prevalent in Indonesia, including in the city of Manado. This study aims to analyse the effectiveness of law enforcement against online gambling crimes and identify factors that are challenging in the enforcement process. The research method used is an empirical approach with data collection techniques through interviews, observations, and documentation studies. The results of the study show that although law enforcement officials have made various efforts to eradicate online gambling, challenges such as regulatory limitations, evolving modus operandi, and limited technological resources are still major obstacles. In addition, the low legal awareness of the community also contributes to the high number of online gambling cases. To increase the effectiveness of law enforcement, a comprehensive strategy is needed that includes regulatory updates, capacity building in the field of digital technology, and education campaigns for the public. With a more synergistic approach between the government, law enforcement officials, and internet service providers, it is hoped that online gambling in Manado City can be minimised.